Ultrassonografia dos testículos e epidídimos de carneiros jovens na fase peri-puberal - AMORIM, Anny Kaline Gomes de Andrade (2010)
Aiming to evaluate the ultrasonographic appearance of testis and epididymis of sheep in pubertal and peripubertal age in order to establish normal parameters for this stage of reproductive development, 38 animals clinically healthy were used, twenty Santa Inês breed and 18 crossbred (Dorper x Santa Inês). In Santa Ines lambs, periodic evaluations of the development of weight, measurements of biometric characteristics of the testes and ultrasound examinations of the testes and epididymis were performed from 84 to 280 days of age, at intervals of 28 days. In crossbreed lambs, the same evaluations were performed from 140 to 280 days. Was used Falco 100 (Pie Medical) ultrasound scanner and linear transducer of 8.0 MHz. Scans were performed in the sagittal, transverse, frontal and oblique planes on the testis and tails of right and left epididymis of each animal, evaluating the echotexture of the testicular parenchyma, mediastinum and epididymis cauda, and measuring the thickness mediastinum and testis width. The testicular parenchyma showed homogeneous echogenicity, ranging from low to moderate, which increased in direct proportion to the age, being higher in pubertal lambs when compared to pre-pubertal. The echogenicity and thickness of the mediastinum increased with age, being classified as diffuse, moderately and highly echogenic. The tail of the epididymis showed hypoechoic appearance in relation to the testicular parenchyma. It was observed mild calcification in the testis parenchyma of five crossbreed lambs as multifocal hyperechoic images. Results of this study showed that ultrasound imaging can be used as an additional resource in the selection and evaluation morphophisiological of breeding sheep in pubertal and peripubertal age , helping to identify and monitoring changes progressive occurring in the testes and epididymis at this stage of reproductive development.